Pengembangan E-Modul Mata Pelatihan Pemetaan Kompetensi dan Indikator Berbasis Flip PDF Corporate Edition dengan Menggunakan Model ADDIE pada Pelatihan Metodologi Pembelajaran di Balai Diklat Keagamaan Surabaya - Rahmawati, Fenny; Leksono, Ibut Priono; Rohman, Ujang (LP. Ma'arif Janggan Magetan, 2023)
This development research aims to: (1) produce teaching material products in the form of Competency Mapping and Indicator Mapping Training Subject E-Modules; (2) find out the feasibility of teaching materials in the form of Competency Mapping and Indicators Training Subject E-Modules, (3) find out the effectiveness of teaching materials in the form of Competency Mapping and Indicators Training Subject E-Modules. The development of e-modules in this study uses the ADDIE model. The ADDIE development model consists of five stages, namely the analysis, design, development, implementation, and evaluation stages. The results of validation of the competency mapping e-module and indicators by design experts obtained a percentage of 92% and was declared very valid. The results of the validation of the competency mapping e-module and indicators by media experts obtained a percentage of 92%, and was declared very valid. The results of validation of the competency mapping e-module and indicators by material experts obtained percentages of 93% and 91%, and were declared very valid. The competence mapping e-module and indicators obtained very good responses from the training participants in small and large group trials with successive percentages of 82% and 83.88%. There is a significant difference between the post test and pre test scores. In the small group trial, the average post-test score was 10.80 points higher than the pre-test score, while in the large group trial, the average post-test score was 32.56 points higher than the pre-test score.